Comparing Reading Aloud and Silent Reading Strategies in Enhancing Reading Comprehension Among Elementary Students - M. Habibie; Winta, Lasti Rahma (Bidayatuna, 2024)
The purpose of this study was to compare the effectiveness of using reading aloud and sustained silent reading strategies on the ability to explain reading content in terms of the opinions/perceptions of high-grade students. This research uses a qualitative approach, with a type of research that is descriptive qualitative. The data collection techniques in this study consisted of (1) an assessment of the ability to explain the content of the reading, (2) interviews with students regarding their perceptions when reading using the reading aloud strategy and sustained silent reading strategy, and (3) documenting the process of reading texts. Based on these data collection techniques, the research instruments used consisted of (1) assessment sheets for the ability to explain reading content, (2) structured interview guide sheets, and (3) documentation of students' reading processes. This research was conducted by Rumbel Azmi Falah Al-mulk, where the research subjects were grade 5 students. The results were based on the student's ability to explain the contents of the reading again and from the interviews that had been conducted related to the comparison between reading aloud and sustained silent reading strategies on the ability to explain the contents. It can be concluded that the sustained silent reading strategy is more effective when used in learning because it makes it easier for students to understand and explain the contents of the reading again.